Hydrogen bonds between methanol and the light liquid olefins 1-pentene and 1-hexene: from application to fundamental science. Issue 28 (24th March 2017) - Zhang, Zhaoxi; Xiao, Tiancun; Al-Megren, Hamid; Aldrees, Saud A.; Al-Kinany, Mohammad; Kuznetsov, Vladimir L.; Kuznetsov, Maxim L.; Edwards, Peter P.
Abstract : Hydrogen bonding is the critical component of a new, sustainable 'Extractive Refining' technology for reducing the olefin content of commercial FCC gasoline. Abstract : We have recently developed a new extraction process for significantly reducing the olefin content in commercial FCC gasoline. To gain insights into the origins of this process, we have investigated the dissolution of the light liquid olefins 1-pentene and 1-hexene in methanol through computer modelling together with NMR spectroscopy. We find two important hydrogen bonding modes for methanol olefin interactions – namely, O–H⋯π and C–H⋯O.